EFFICACY AND SAFETY OF ADALIMUMAB VERSUS INFLIXIMAB IN PATIENTS SUFFERED FROM MODERATE TO SEVERE ACTIVE ULCERATIVE COLITIS - Retracted, Article (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Article Retracted